2003
DOI: 10.1023/a:1021713711160
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Microorganisms isolated from soil samples were screened for their ability to degrade various biodegradable polyester-based plastics. The most active strain, designated as strain TB-13, was selected as the best strain for degrading these plastics. From its phenotypic and genetic characteristics, strain TB-13 was closely related to Paenibacillus amyloyticus. It could degrade poly(lactic acid), poly(butylene succinate), poly(butylene succinate-co-adipate), poly(caprolactone) and poly(ethylene succinate) but not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(47 citation statements)
references
References 20 publications
0
46
0
1
Order By: Relevance
“…Aliphatic polyesters are considered the most promising biodegradable synthetic polymers that have been developed as the alternative of conventional thermoplastics. 1 They have received much attention because they can be degraded completely in the environment without forming any toxic products. 2 Otherwise, wound sutures, staples, and medical devices for internal drug deposition made of biodegradable polymers are able to dissolve and adsorbed in to the human body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aliphatic polyesters are considered the most promising biodegradable synthetic polymers that have been developed as the alternative of conventional thermoplastics. 1 They have received much attention because they can be degraded completely in the environment without forming any toxic products. 2 Otherwise, wound sutures, staples, and medical devices for internal drug deposition made of biodegradable polymers are able to dissolve and adsorbed in to the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have described the isolation and characterization of microorganisms that can degrade polyester-based biodegradable plastics. 1,[16][17][18][19][20] Known to be responsible for the decomposition of a wide array of substrates in soil, Actinomycetes also play an important role in the biodeterioration of synthetic rubber or plastics. 21,22 Other species in soil, including Acidovorax facilis, Variovorax paradoxus, Bacillus, Streptomyces, and several mold strains were also found degrading polyesters.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other petrochemical-based resins that take centuries to degrade after disposal, these polymers break down rapidly into carbon dioxide, water, and humus under appropriate conditions when they are exposed to the combined attack of water and micro-organisms. [2,3] These products also meet advanced composting standards and typically break down in twelve weeks under aerobic conditions. [4] In this direction, poly[(butylene succinate)-co-adipate] (PBSA) is among the most promising polymer.…”
Section: Introductionmentioning
confidence: 99%
“…However, one bioplastic-degrading bacterium was isolated and was preliminarily classified as Paenibacillus sp. Previously, Teeraphatpornchai et al (2003) reported that Paenibacillus amyloticus strain TB13 could degrade PLA, PBS, PCL and PES but not PHB-covalerate. This study was the first report that Cladosporium and Purpureocillium fungi could form clear zones on PLA, PBS and PCL agar plates.…”
Section: Discussionmentioning
confidence: 99%